Evolutionary collaborative partnership model (ECPM): The East African elearning provider's project-based legitimization strategy - Tossy, Titus (International Journal of Computing and ICT Research, 2024)
Article published by the International Journal of Computing and ICT Research Vol. 8, Issue 1 pp 37 - 48.